2016
DOI: 10.1177/0271121416637597
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Dialogic Reading Intervention for Preschool Children With Autism Spectrum Disorder

Abstract: We examined the effect of a modified dialogic reading intervention on levels of verbal participation and vocabulary growth in nine preschool children with autism spectrum disorder (ASD) using single-case design methodology. Baseline book reading resulted in consistently low levels of verbal participation followed by an immediate increase in verbal participation during dialogic book reading sessions for all children. Dialogic reading also resulted in greater gains in book-specific vocabulary for all children, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 28 publications
7
127
0
5
Order By: Relevance
“…While previous studies have used visual prompts and the provision of answers by pointing (Fleury et alia, 2014;Whalon et alia, 2015;Whalon et alia, 2016), our present study expands the results of Fleury and Schwartz (2017) in demonstrating that it is possible to use verbal prompts to help children with ASD answer questions about the story during dialogic reading. Visual prompts may lead a conversation to center on illustrations and hinder progress towards plot-based dialogue (of course, this being an issue depends on the objectives of the activity).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…While previous studies have used visual prompts and the provision of answers by pointing (Fleury et alia, 2014;Whalon et alia, 2015;Whalon et alia, 2016), our present study expands the results of Fleury and Schwartz (2017) in demonstrating that it is possible to use verbal prompts to help children with ASD answer questions about the story during dialogic reading. Visual prompts may lead a conversation to center on illustrations and hinder progress towards plot-based dialogue (of course, this being an issue depends on the objectives of the activity).…”
Section: Discussionsupporting
confidence: 54%
“…Recently, Fleury and Schwartz (2017), like Guevara et alia (2017), used verbal prompts in a least-to most prompting hierarchy to help preschool children with ASD to elaborate their answers during DR implemented by para-educators. They tested the effects of the intervention on verbal participation and book-specific vocabulary.…”
Section: What This Paper Adds?mentioning
confidence: 99%
“…The fourth study was conducted with pairs of children with ASD and found that all four participating children had fewer incorrect responses and more frequent correct, spontaneous responses in comparison to baseline (Whalon, Martinez, Shannon, Butcher, & Hanline, 2015). The final study (Fleury and Schwartz, 2016) examined 1:1 interventions with 9 preschoolers with ASD and found greater gains in book-specific vocabulary and increased responses to adult question prompts for all children in comparison to baseline book reading session. This initial evidence of efficacy supports our examination of interactive book reading with larger samples of children with ASD.…”
Section: Emergent Literacy Interventionsmentioning
confidence: 99%
“…61 At present, preschool interventions that address language comprehension of children with ASD emphasize shared reading. Shared reading interventions have improved spontaneous verbalizations, [62][63][64] vocabulary, 64 and correct responding. 65,66 Dialogic reading (DR) is a shared reading intervention that enhances the oral language skills necessary for future reading comprehension, 5 and is well supported in the literature.…”
Section: Manipulating Sounds In Wordsmentioning
confidence: 99%
“…1 Fleury and colleagues found that DR improved the verbal participation and vocabulary of children with ASD. 63,64 Whalon and colleagues adapted DR to include systematic instructional procedures shown to support the learning of children with ASD, including visual supports, prompts to promote joint attention, and a least-to-most prompting hierarchy.…”
Section: Manipulating Sounds In Wordsmentioning
confidence: 99%